2017
DOI: 10.1016/j.jep.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Piper sarmentosum Roxb. produces antidepressant-like effects in rodents, associated with activation of the CREB-BDNF-ERK signaling pathway and reversal of HPA axis hyperactivity

Abstract: Ethnopharmacological relevance: There are many plants of genus Piper which have been reported to induce antidepressant-like effects, Piper sarmentosum (PS) is one of them. PS is a Chinese herbal medicine and a traditional edible vegetable. Materials and Methods:In the present study, the antidepressant-like effects of PS extracts and the ethyl acetate fraction of PS extracts (PSY) were assessed using the open field test (OFT), forced swimming test (FST), and tail suspension test (TST) in mice. Furthermore, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Functional properties of P. sarmentosum as antidepressant were exhibited in rodent animal model by means of hypothalamic-pituitary-adrenal axis regulation [373]. In the study of Li et al [373] these properties of the P. sarmentosum extract and its ethyl acetate fraction (PSY) were investigated by using several parameters including forced swimming test, open field test, and tail suspension test in mice.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional properties of P. sarmentosum as antidepressant were exhibited in rodent animal model by means of hypothalamic-pituitary-adrenal axis regulation [373]. In the study of Li et al [373] these properties of the P. sarmentosum extract and its ethyl acetate fraction (PSY) were investigated by using several parameters including forced swimming test, open field test, and tail suspension test in mice.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
“…Functional properties of P. sarmentosum as antidepressant were exhibited in rodent animal model by means of hypothalamic-pituitary-adrenal axis regulation [373]. In the study of Li et al [373] these properties of the P. sarmentosum extract and its ethyl acetate fraction (PSY) were investigated by using several parameters including forced swimming test, open field test, and tail suspension test in mice. The results showed that treatment of mice with either P. sarmentosum extracts at 100 and 200 mg/kg or PSY at 12.5–50 mg/kg doses resulted in potent antidepressant effects, which is similar to response obtained by 20 mg/kg conventional therapeutic drug fluoxetine.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
“…Anyu Peibo Capsule is a new antidepressant, extracted from Piper Laetispicum C.D C. (Piperaceae) which is a climbing glabrous plant grows in the south of China and has been used for invigorating circulation and reducing detumescence, stasis, and analgesic [8,9,10,11] . The pharmacodynamics of Anyu Peibo Capsule were assessed in health volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…NR2B-containing channels predominantly signal via extracellular signal-regulated kinase (ERK) (17), a pivotal transcription regulator of the mitogen-activated protein kinase family (18). One potential effector of ERK signaling involved in CUMS-induced depression is cAMP response element binding protein, a transcription factor essential for neurogenesis, neuronal survival, and neuroplasticity (19) and, for which, the activity (20) and phosphorylation (21) are linked to the responsiveness to antidepressants.…”
Section: Introductionmentioning
confidence: 99%